Stability-indicating Reversed-phase Liquid Chromatographic Method for Simultaneous Determination of Losartan Potassium and Ramipril in Tablets - Kollipara, S. (Medknow Publications & Media Pvt Ltd, 2012)
A stability-indicating reversed-phase liquid chromatographic method has been developed and validated for simultaneous determination of losartan potassium and ramipril. Separations were achieved using a C(18) column with mobile phase consisting of acetonitrile and (0.2% v/v, pH 2.5) aqueous trifluoroacetic acid (45:55, v/v) in isocratic mode at 1 ml/min flow rate. Column effluent was monitored at 210 nm using a UV detector. The method was validated for selectivity, linearity, accuracy, precision, sensitivity and robustness. Novel microwave-assisted forced degradation technique was employed for evaluation of selectivity. The method demonstrated excellent linearity for losartan potassium and ramipril with regression coefficients of 0.9999 and 0.9998, respectively. The linearity range was found to be 62.5-5000 ng/ml and 125-10,000 ng/ml with the mean percentage recoveries of 100.36% (±2.27) and 100.16% (±3.33) for losartan potassium and ramipril, respectively. In a robustness study, a full factorial design revealed that the analytical response remains unaffected by small variations in the critical chromatographic factors. The method was found to be sensitive with quantification limits of 44.30 and 79.93 ng/ml for losartan potassium and ramipril. The method was successfully employed for the determination of losartan potassium and ramipril in commercially available and in-house prepared tablets.